PENGEMBANGAN SISTEM PEMESANAN TIKET WAYANG ORANG SRIWEDARI MENGGUNAKAN PAYMENT GATEWAY MIDTRANS - Vera Wati; Nisrina Yulia Setyawati; Wartono Wartono (Badan Penelitian dan Pengabdian Masyarakat (BP2M) STMIK Syaikh Zainuddin NW Anjani, 2025)
ABSTRACT Cultural tourism is one of the travel options that can be chosen by the community. Cultural destinations usually emphasize the arts or culture in an area, like one of the cultural destinations in Surakarta City, namely Wayang Orang Sriwedari. Wayang Orang Sriwedari is a destination with quite high enthusiasm and is currently quite popular among young people. With the current operational conditions, several complaints have emerged, such as the lack of information provided regarding the synopsis of the show to the occurrence of queues in front of the ticket counter. Some people have also started asking how to buy tickets online. To overcome the complaints and problems that occur, a ticket ordering information system for Wayang Orang Sriwedari performances was created using the waterfall method. This system is also integrated with midtrans so that it supports multi-payment payment transactions. System testing was carried out on the payment endpoint connection and the results showed that the integration with the midtrans payment gateway was running well. The results of the functionality test with the black box test also showed that the system could work well and provide the appropriate output. Keywords: Ticket Booking System, Wayang Orang Sriwedari, Midtrans